Public participation in town-planning applications: Tlokwe Local Municipality as a case study - Puren, Karen; Goosen, Tjaart; Jordaan, Tarina (Department of Urban and Regional Planning, University of the Free State, 2013)
Although public participation is deemed important in South Africa, negative perceptions of its legitimacy are widely acknowledged. Inclusive town-planning processes, as instruments to address inequality, have a significant role in enhancing democracy. This article reports on a study done from a communicative planning perspective, with the aim to investigate the influence of public participation in town planning by means of an analysis of town-planning application procedures between 1992-2008 in the Tlokwe Local Municipality, North-West province, South Africa. The results indicate that only 6% of all commentary on planning applications consists of objections from the public. Technically motivated objections and town-planning firms had the most influence on planning outcomes. This seems to indicate reactive and consultative participation wherein the final decision resides with the local authority. It appears that public participation’s idealistic ‘feel good’ mask does not live up to the expectations of an empowered civil society.

Alhoewel publieke deelname as belangrik geag word in Suid-Afrika, word negatiewe persepsies oor die egtheid daarvan erken. Inklusiewe stadsbeplanningsprosesse, as instrumente om ongelykheid aan te spreek, speel ‘n betekenisvolle rol in die versterking van demokrasie. Hierdie artikel doen verslag oor ‘n studie wat gedoen is vanuit ‘n kommunikatiewe beplanningsperspektief en beoog om die invloed van publieke deelname in stadsbeplanning te ondersoek deur middel van ‘n analise van stadsbeplanningsaansoekprosedures tussen 1992-2008 in die Tlokwe Plaaslike Munisipaliteit, Noordwes-provinsie, Suid-Afrika. Die resultate toon dat van alle kommentare op beplanningsaansoeke is slegs 6% besware vanaf die publiek. Tegniesgemotiveerde besware en stadsbeplanningsfirmas het die meeste invloed op beplanningsuitkomstes gehad. Dit blyk dat deelname reaktief en konsulterend is, met die finale besluite in die hande van die plaaslike munisipaliteit. Publieke deelname se idealistiese ‘voel goed’ masker blyk nie te voldoen aan die verwagtinge van ‘n bemagtigde burgerlike samelewing nie.

Le ha bohlokoa ba tshebedisano mmoho le sechaba e boledisoa ho ba bohlokoa ka hara naha ya Afrika Borwa, shebisano tse negethifi tsa hore na ehlile ya sebetsa dia hlahella. Merero ya teropo e nang le tshebelisano mmoho le sechaba e sebetsana le taba tsa hore ba bang ba sechaba ba utloe ba nyenyefaditsoe ho feta ba bang ebile e eketsa taba ya hore batho ba phedisane mmoho ba na le khotso. Serapa sena se bontsa thuto e ileng ya etsoa ho shebisisa tshebelisano mmoho le sechaba mererong ya teropo mekhoa ea Tlokwe Local Municipality e North West Province, Afrika Borwa ho tloha selemong sa 1992 ho isa ho sa 2008. Sephetho sa thuto ena se bontshitse hore ke 6% fela eo sechaba e khonneng ho e kenya tabeng ya ho rera teropo ya teng. Nnete ke hore lifeme tsa merero ya diteropo ke tsona tse nang le matla a mangata a hotre zana teropo e reroe joang. Sena se bontshitse tshebedisano mmoho le sechaba fela qeto e le ea masepala. Tshebedisano mmoho le sechaba ke nthoe e bonahalang e le ntle ka kellellong fela bo nneteng e sa sebetse.
Keywords: Public participation; Town-planning; Democracy; Inequality